Migratory Helicoverpa armigera (Lepidoptera: Noctuidae) Exhibits Marked Seasonal Variation in Morphology and Fitness. Issue 3 (16th May 2019) - Zhou, Yan; Wu, Qiulin; Zhao, Shengyuan; Guo, Jianglong; Wyckhuys, Kris A G; Wu, Kongming
Abstract: Many insects adopt seasonal, trans-latitudinal migration in response to altering climatic conditions, resource availability or reproductive requirements. Though the migration behavior of the cotton bollworm, Helicoverpa armigera (Hübner)(Lepidoptera: Noctuidae), has been well-studied, little is known about the extent of intra-specific variation between northward- and southward-migrating individuals. In this study, we captured H. armigera adults along the species' migration route during 2017–2018 to determine seasonal variability in their morphology, flight capability, and reproductive performance. Northward migrants have broader, longer bodies and are 1.33 times heavier than southward migrants, hinting at a comparatively higher allocation of resources in the abdomen. Accordingly, the former migrants engaged in longer flights, had greater reproductive capacity and a longer lifespan than southward ones. As northward migrants originate from favorable environmental conditions, their fitness is higher than that of the southward cohorts that develop on less favorable host plants and in perhaps more adverse climatic or ecological conditions. Northward H. armigera migrants thus possess an advantageous morphology that benefits habitat colonization and resource exploitation. Our work offers a novel perspective on the ecological and reproductive benefits of long-distance migration and can aid the development of population monitoring and forecasting methods for this globally important agricultural pest.